Changes in 14CO2 assimilate partitioning into primary photosynthetic metabolites in flowering and non-flowering rose (Rosa damascena Mill) plants - Sharma, N K Srivastava, A Misra, S (Journal of Spices and Aromatic Crops, 2001)
Changes in 14CO2 assimilation into primary photosynthetic metabolites in developing leaves of flowering and non-flowering plants of rose have been investigated. Total 14C assimilated increased up to 4.5 h and then declined in flowering plants, while in non-flowering plants maximum assimilation was observed at 1.5 h and thereafter it steadily declined. First and second leaf (from apex) in flowering shoot assimilated maximum photosynthate which continued to increase with time, whereas second leaf of non-flowering plants assimilated maximum CO, which decreased with time. Maximum photosynthate translocation to flower occurred at 3 h after feeding. A significant portion of photosynthate remained untranslocated in stems of non-flowering plants. Within leaves, maximum metabolite labeled was sugars in flowering shoot at 1.5 h, which declined later, whereas amino acids and organic acids level increased upto 4.5 h. Very little metabolite remained untranslocated in stem. In non-flowering plants, level of these metabolites decreased with time, however high level of metabolites remained in stem. Contrasting and reverse pattern of carbon assimilation was observed between flowering and non-flowering shoots. In nonflowering shoot, sugars and amino acids contents were significantly negatively correlated, whereas a significant positive correlation was observed in flowering shoot. The flowering and non-flowering shoots significantly differed in partitioning of primary photosynthetic metabolites between leaf, stem and flower.